Rising rates of hospital-onset Klebsiella spp. and Pseudomonas aeruginosa bacteraemia in NHS acute trusts in England: a review of national surveillance data, August 2020–February 2021. (January 2022) - Sloot, R.; Nsonwu, O.; Chudasama, D.; Rooney, G.; Pearson, C.; Choi, H.; Mason, E.; Springer, A.; Gerver, S.; Brown, C.; Hope, R.
Summary: Increases in hospital-onset Klebsiella spp. and Pseudomonas aeruginosa bacteraemia rates in England were observed between August 2020 and February 2021 to the highest levels recorded since the start of mandatory surveillance in April 2017. Cases were extracted from England's mandatory surveillance database for key Gram-negative bloodstream infections. Incidence rates for hospital-onset bacteraemia cases increased from 8.9 ( N =255) to 14.9 ( N =394) per 100, 000 bed-days for Klebsiella spp. [incidence rate ratio (IRR) 1.7, P <0.001], and from 4.9 ( N =139) to 6.2 ( N =164) per 100, 000 bed-days for P. aeruginosa (IRR 1.3, P <0.001) (August 2020–February 2021). These incidence rates were higher than the average rates observed during the same period in the previous 3 years. These trends coincided with an increase in the percentage of hospital-onset bacteraemia cases that were also positive for severe acute respiratory syndrome coronavirus-2.